2023
DOI: 10.1101/2023.05.23.542024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Multi-Epitope/CXCL11 Prime/Pull Coronavirus Mucosal Vaccine Boosts the Frequency and the Function of Lung-Resident CD4+and CD8+Memory T Cells and Protects Against COVID-19-like Symptoms and Death Caused by SARS-CoV-2 infection

Latifa Zayou,
Swayam Prakash,
Nisha Rajeswari Dhanushkodi
et al.

Abstract: The pandemic of the coronavirus disease 2019 (COVID-19) has created the largest global health crisis in almost a century. Following exposure to SARS-CoV-2, the virus particles replicate in the lungs, induce a cytokine storm and potentially cause life-threatening inflammatory disease. Low frequencies of function SARS-CoV-2-specific CD4+ and CD8+ T cells in the lungs of COVID-19 patients were associated with severe cases of COVID-19. The apparent low level of T cell-attracting CXCL9, CXCL10, and CXCL11 chemokine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…A detailed comparison of the early innate immunity events that occur after administration of the combined mRNA/LNP vaccine vs. the Spikealone mRNA/LNP vaccine would help elucidate the underlying mechanism behind the strong protective immunity induced by the combined mRNA/LNP vaccine.The antiviral B and T cell immune mechanisms reported in this study, are expected to inform the design of next-generation broad-spectrum pan-Coronavirus vaccines1,4,5,6,19 . The present results from the hamster model confirm our and others recent reports in mouse models that increased frequencies of lung-resident IFN-γ + TNF-α + CD4 + and IFN-γ + TNF-α + CD8 + T EFF cells specific to common antigens protected against multiple SARS-CoV-2 VOCs1,3,27 . Interferons restrict SARS-CoV-2 infection in human airway epithelial cells2,62 .…”
supporting
confidence: 92%
See 2 more Smart Citations
“…A detailed comparison of the early innate immunity events that occur after administration of the combined mRNA/LNP vaccine vs. the Spikealone mRNA/LNP vaccine would help elucidate the underlying mechanism behind the strong protective immunity induced by the combined mRNA/LNP vaccine.The antiviral B and T cell immune mechanisms reported in this study, are expected to inform the design of next-generation broad-spectrum pan-Coronavirus vaccines1,4,5,6,19 . The present results from the hamster model confirm our and others recent reports in mouse models that increased frequencies of lung-resident IFN-γ + TNF-α + CD4 + and IFN-γ + TNF-α + CD8 + T EFF cells specific to common antigens protected against multiple SARS-CoV-2 VOCs1,3,27 . Interferons restrict SARS-CoV-2 infection in human airway epithelial cells2,62 .…”
supporting
confidence: 92%
“…The Coronavirus disease 2019 (COVID-19) pandemic has created one of the largest global health crises in nearly a century 1,2,3,4,5,6 . As of January 2024, the number of confirmed SARS-CoV-2 cases has reached over 770 million, and COVID-19 disease caused nearly 7 million deaths 1,5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is biologically plausible—antibody alone might not explain the protection provided by inactivated vaccines, as T-cell responses and potentially non-neutralising antibodies to internal virus genes, such as the nucleocapsid, 15 might also play a role, especially against strains such as omicron, which have high escape rate from neutralising antibody elicited by the ancestral virus. For T-cell response, previous studies using vaccinated transgenic mice with humanised ACE2 receptor showed that CD4 + and CD8 + T cells protected against severe disease by ancestral strain 16 and CD4 + T cells conferred heterologous protection against the beta variant, 17 and experiments using human samples suggested T-cell cross-reactivity against omicron. 18 , 19 Our study provides a head-to-head comparison of T-cell response between homologous and heterologous vaccination, and shows that both homologous and heterologous third doses could boost T-cell responses in people with two previous doses of CoronaVac.…”
Section: Discussionmentioning
confidence: 99%